Analisis Determinan Fraud Prevention (Studi Empiris Pada Badan Usaha Milik Daerah di D.I Yogyakarta dan Jawa Tengah) - Ilham Maulana Saud; Alfin Taufiqul Hakim; Lulu Dyar (Jurnal Akuntansi Keuangan dan Bisnis, 2020)
This research has a purpose to analyze the influence of proactive fraud audit, whistleblowing system, and internal control system of fraud prevention with morality as a moderating variable. The subject in this research is employees who work in Badan Usaha Milik Daerah (BUMD) in Yogyakarta and Central Java. The number of samples in this research were 70 respondent that has been chosen by using a purposive sampling method. The type of data used is primary data. The results of the research show that proactive fraud audits did not affect fraud prevention. The whistleblowing system has a positive influence on fraud prevention. The internal control system has a positive influence on fraud prevention. Morality strengthens the influence of proactive fraud audits on fraud prevention. Morality does not moderate the influence of the whistleblowing system on fraud prevention. Morality does not moderate the influence of the internal control system on fraud prevention. Keywords: Proactive fraud audit, Whistleblowing System, Internal Control System, Fraud Prevention, Morality.